Seven natural wonders of Asia and the Middle East - Woods, Michael, 1946-; Woods, Mary B., (Mary Boyle), 1946- (Minneapolis, MN : Twenty-First Century Books, 2009)
Explores seven natural wonders of Asia and the Middle East including Mount Everest, the Gobi Desert, Mount Fuji, Sumatra Rain Forest, the Dead Sea, Cappadocia, and the Chocolate Hills.
Includes bibliographical references (p. 75-77) and index.
6.5
5-8
Keywords: Landforms -- Asia -- Juvenile literature; Landforms -- Middle East -- Juvenile literature; Landscape -- Asia -- Juvenile literature; Landscape -- Middle East -- Juvenile literature; Landforms; Landscape; Landforms; Scenery; Asia; Middle East; Asia; Middle East